2007
DOI: 10.1021/ma071019q
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched Poly(ferrocenylphenylenes):  Synthesis, Characterization, Redox Activity, Metal Complexation, Pyrolytic Ceramization, and Soft Ferromagnetism

Abstract: Hyperbranched poly(ferrocenylphenylenes) (hb-PFPs) with high molecular weights were synthesized by the copolycyclotrimerizations of (E,E)-1,1‘-bis[2-(4-ethynylphenyl)vinyl]ferrocene (1) with (E)-1-[2-(4-ethynylphenyl)vinyl]ferrocene (2) catalyzed by TaCl5−Ph4Sn at room temperature in high yields (up to 97%). Effects of reaction conditions, such as monomer and catalyst concentrations, reaction time and molar feed ratio (r 1 / 2 ), on the copolycyclotrimerization were investigated. Solubility of the copolymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 40 publications
2
31
0
Order By: Relevance
“…Since ferrocene, η 6 ‐benzene‐η 5 ‐cyclopentadienyliron and alkyne–cobalt carbonyl complexes are known to possess electrochemical behavior, we used cyclic voltammetry to determine if this would be evident in our structures 21, 24. The cyclic voltammogram of complex 7 (Figure 1C) displayed an E 1/2 = 0.69 V (vs. Ag/AgCl) corresponding to the reversible oxidation of the ferrocene moiety to a ferrocenium ion moiety.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since ferrocene, η 6 ‐benzene‐η 5 ‐cyclopentadienyliron and alkyne–cobalt carbonyl complexes are known to possess electrochemical behavior, we used cyclic voltammetry to determine if this would be evident in our structures 21, 24. The cyclic voltammogram of complex 7 (Figure 1C) displayed an E 1/2 = 0.69 V (vs. Ag/AgCl) corresponding to the reversible oxidation of the ferrocene moiety to a ferrocenium ion moiety.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Al‐Badri and Tew23 reported that oxonorbornene containing cobalt carbonyl protected alkynes could be polymerized using the third generation Grubbs' catalyst. Also, Tang and coworkers24 has found that ceramics prepared from cobalt carbonyl containing ferrocene compounds possess interesting ferromagnetic properties. With this in mind, the preparation of organoiron polynorbornenes containing µ‐alkyne‐bis(tricarbonylcobalt) has the potential to produce functional materials with unique electrical and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The redox patterns are complicated compared with that of ferrocene (Figure S22, Supporting Information) presumably due to the presence of various electrically active functional groups including iodo, amino acid, and phenyleneethynylene moieties. The peaks around 0.05 V are assignable to ferrocene moieties in the charts of 1 m , poly( 1 m ‐ 2 ), poly( 1 m ‐ 3 ), although the reversible redox patterns are not clear compared to previously reported ferrocene‐containing π‐conjugated polymers such as poly(ferrocenylenevinylene) substituted with tert ‐butyl groups and hyperbranched poly(ferrocenylphenylenes) . It is considered that intermolecular interactions such as hydrogen bonding and π‐stacking are also responsible for unclarity in the redox peaks of the present monomers and polymers.…”
Section: Resultsmentioning
confidence: 99%
“…Ferrocene‐containing polymers were synthesized and applied in numerous field, while there are only a few reports of the application of such polymers in solid composite propellants as BR catalysts, even though ferrocene‐containing polymers and related materials present enormous potentiality in this field.…”
Section: Synthesis Of Ferrocene‐containing Polymers and Derivatives Umentioning
confidence: 99%